Long‐term efficacy and safety of canagliflozin over 104 weeks in patients aged 55–80 years with type 2 diabetes. Issue 3 (12th January 2015) - Bode, B.; Stenlöf, K.; Harris, S.; Sullivan, D.; Fung, A.; Usiskin, K.; Meininger, G.
<x xml:space="preserve">Abstract</x> Aims The long‐term efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, was evaluated over 104 weeks in patients aged 55–80 years with type 2 diabetes mellitus (T2DM) inadequately controlled on a stable antihyperglycaemic agent regimen. Methods In this randomized, double‐blind, phase III study, patients received canagliflozin 100 or 300 mg or placebo once daily during a 26‐week core period (N = 714) and a 78‐week extension period (n = 624). Efficacy endpoints at week 104 included change from baseline in glycated haemoglobin (HbA1c), fasting plasma glucose (FPG) and systolic blood pressure, and percent change from baseline in body weight and fasting plasma lipids. Safety was assessed by adverse event (AE) reports. Results At week 104, canagliflozin 100 and 300 mg were associated with reductions in HbA1c versus placebo (−0.32 and −0.43% vs 0.17%, respectively; overall mean baseline, 7.7%) and more patients achieved HbA1c <7.0% with canagliflozin 100 and 300 mg than with placebo (35.8 and 41.9% vs 20.3%, respectively). Reductions in FPG, body weight and systolic blood pressure, and increases in high‐density lipoprotein cholesterol (HDL‐C) and low‐density lipoprotein cholesterol (LDL‐C) were seen with canagliflozin compared with placebo. The overall incidence rates of AEs over 104 weeks were 88.0, 89.8 and 86.1% with canagliflozin 100 and 300 mg and placebo, respectively; serious AE rates were low across treatment groups. The incidence rates of urinary tract infections, genital mycotic infections and osmotic diuresis– and volume depletion–related AEs were higher with canagliflozin than with placebo. Conclusion Canagliflozin improved glycaemic control, reduced body weight and systolic blood pressure, and was generally well tolerated in patients aged 55–80 years with T2DM over 104 weeks.